Water Symbolism in the Religious Life of Man - Pereira, Theodore (Journal of Dharma, 1984)
One of the very significant truths that Comparative History of Religion has been instrumental in spotlighting in the recent past is the important role played by symbols in the religious life of man. With an enormous fund of evidence at its disposal this discipline has proceeded to show how the many symbolic elements and actions utilized by man in his cultic life were not more or less indifferent phenomena forcefully impregnated with a meaning for which they were in no way prepared, but rather quite meaningful in themselves. If particular objects and actions, such as fire and offerings, oil and anointings, water and blessings had a definite meaning in the religious life of man, it could only be because these objects and actions already possessed a natural symbolism of their own, a particular meaning proper to them before they were taken up and employed by man for translating his innermost thoughts and experiences into divine-human relational categories.